Regulation of Immune Responses by the Neonatal Fc Receptor and Its Therapeutic Implications - Rath, Timo; Baker, Kristi; Pyzik, Michal; Blumberg, Richard S. (Frontiers in Immunology, 2015)
As a single receptor, the neonatal Fc receptor (FcRn) is critically involved in regulating albumin and IgG serum concentrations by protecting these two ligands from degradation. In addition to these essential homeostatic functions, FcRn possesses important functions in regulating immune responses that are equally as critical and are increasingly coming to attention. During the first stages of life, FcRn mediates the passive transfer of IgG across the maternal placenta or neonatal intestinal walls of mammals, thereby conferring passive immunity to the offspring before and after birth. In fact, FcRn is one of the very few molecules that is known to move from luminal to serosal membranes of polarized cells that form epithelial barriers of the lung and intestines. Together with FcRn’s recently explored critical role in eliciting MHC II presentation and MHC class I cross-presentation of IgG complexed antigen, this renders FcRn capable of exerting broad and potent functions in regulating immune responses and immunosurveillance at mucosal sites. Further, it is now clear that FcRn dependent mucosal absorption of therapeutic molecules is a clinically feasible and potent novel route of non-invasive drug delivery, and the interaction between FcRn and IgG has also been utilized for the acquisition of humoral immunity at mucosal sites. In this review we begin by briefly summarizing the basic knowledge on FcRn expression and IgG binding, then describe more recent discoveries pertaining to the mechanisms by which FcRn orchestrates IgG related mucosal immune responses and immunosurveillance at host-environment interfaces within the adult organism. Finally, we outline how the knowledge of actions of FcRn at mucosal boundaries can be capitalized for the development and engineering of powerful mucosal vaccination strategies and novel routes for the non-invasive delivery of Fc-based therapeutics.